2018
DOI: 10.1039/c8nr02192a
|View full text |Cite
|
Sign up to set email alerts
|

Microneedles integrated with a triboelectric nanogenerator: an electrically active drug delivery system

Abstract: In this study, a combined system of microneedles and a triboelectric nanogenerator (TENG) has been developed for drug delivery. A triboelectric device, which converts mechanical energy into alternating current (AC), was chosen to replace the electrophoresis (EP) effect. To directly generate triboelectricity from salmon deoxyribonucleic acid (SDNA)-based microneedles, a triboelectric series of SDNA film and chargeable polymers (polyimide and Teflon) was studied. The electrical output of the two charged polymers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 45 publications
(27 citation statements)
references
References 48 publications
0
27
0
Order By: Relevance
“…PDMS (Sylgard 184; Dow Corning, Midland, MI, USA) prepared by mixing elastomer and curing agent in a ratio of 10: 1 was poured onto a master stamp. The molds were cured at 50 °C for 2 h. The PDMS mold was then separated from the stamp 10,11,42 .…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…PDMS (Sylgard 184; Dow Corning, Midland, MI, USA) prepared by mixing elastomer and curing agent in a ratio of 10: 1 was poured onto a master stamp. The molds were cured at 50 °C for 2 h. The PDMS mold was then separated from the stamp 10,11,42 .…”
Section: Methodsmentioning
confidence: 99%
“…In vitro drug release. Gelatin hydrogel (10 wt%; Sigma Aldrich, gel strength ~300 g Bloom, Type A) derived from porcine skin was used as the model tissue for the drug release studies 11,43 . The polymer membrane (Parafilm M, American National Can, Chicago, IL) was pierced with microneedles and placed on the hydrogel surface.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, our group developed a drug delivery system with salmon DNA and hyaluronic acid drug-embedded MNs, and achieved higher drug delivery efficiency by applying physical enhancers, including electricity, ultrasound, and combinations thereof [ 26 , 27 , 28 ]. However, we found that it is also critical to efficiently control the amount of drugs delivered to the body and avoid unnecessary drugs (like drugs on the patch backplate) [ 29 ].…”
Section: Introductionmentioning
confidence: 99%